2017
DOI: 10.12659/msm.905370
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of lncRNA X Inactive Specific Transcript (XIST) Suppresses Cell Proliferation and Enhances Radiosensitivity by Upregulating mir-29c in Nasopharyngeal Carcinoma Cells

Abstract: BackgroundLncRNA X inactive specific transcript (XIST) was reported to function as an oncogene in nasopharyngeal carcinoma cells (NPC) by sponging miR-34a-5p. However, the role of XIST in modulating the radiosensitivity of NPC cells and its mechanism still remain undefined.Material/MethodsThe expressions of XIST and miR-29c in NPC cells were evaluated by qRT-PCR. CNE1 and CNE2 cells were transfected with si-XIST, pcDNA-XIST, miR-29c mimics, anti-miR-29c, or respective controls by Lipofectamine 2000. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Through bioinformatics analysis and experimental results, we identified lncRNA XIST as a sponge of miR‐142‐5p. XIST widely exerts oncogenic properties in lung adenocarcinoma, nasopharyngeal carcinoma and colorectal cancer . In the present study, we first found the association of XIST with miR‐142‐5p in OA.…”
Section: Discussionmentioning
confidence: 99%
“…Through bioinformatics analysis and experimental results, we identified lncRNA XIST as a sponge of miR‐142‐5p. XIST widely exerts oncogenic properties in lung adenocarcinoma, nasopharyngeal carcinoma and colorectal cancer . In the present study, we first found the association of XIST with miR‐142‐5p in OA.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 5 years, the mechanism of lncRNA and miRNA in the progression, radioresistance, drug resistance, and angiogenesis of NPC has been studied. 184,[205][206][207] The role of lncRNAs and miRNAs in different NPC cell lines and the corresponding mechanisms have been, respectively, listed in Tables 1 and 2. The anti-cancer effect Recent studies have found that some microRNAs and lncRNAs in tumor tissues are downregulated and show negative regulation of pathological activities of NPC.…”
Section: Non-coding Rna Related To Targeted Therapy Of Npcmentioning
confidence: 99%
“…The knockdown of lncRNA X inactive-specific transcript (XIST) could upregulate miR-29c, resulting in the inhibition of DNA damage repair and an increase of the radiosensitivity of NPC cells. 206 Antidifferentiation non-coding RNA (ANCR) could regulate PTEN expression epigenetically to promote radioresistance. 226 Besides, lncRNA MALAT1 modulates cancer stem cell activity of NPC and induces radioresistance via regulating the miR-1/slug axis.…”
Section: Non-coding Rna Related To Targeted Therapy Of Npcmentioning
confidence: 99%
“…Next, the fluorescent intensity was observed and photographed under a fluorescence inverted microscope (magnification, ×200; CX41-12C02, Olympus Optical Co., Ltd., Tokyo, Japan) following 48 h transfection. The transfection efficiency was calculated according to the following formula: Transfection efficiency (%) = number of cells with green fluorescent protein (GFP)/total cell number ×100% (17,18). A total of 5 high-power fields were randomly selected, and the mean values were determined.…”
Section: Methodsmentioning
confidence: 99%